PERAN SERIKAT PEKERJA DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 PADA SEKTOR INDUSTRI OTOMOTIF - Haspul Naser; Budi Safari; Kunto Atmojo (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
The purpose of this study was to determine the partnership model between Trade Unions and Management in the face of the Industrial Revolution 4.0. The total sample used was 100 employees in the field of vehicle assembly. The processed data produced there is a "Very Strong" influence between Employee Readiness on the Industrial Revolution 4.0. The results of the analysis obtained the results of the partial t test, the t value of 37.640 t table 1.660 which means that the readiness of employees has a very strong influence on the Industrial Revolution variable. While the correlation results show a value of 0.967, which indicates that there is a very strong influence between employee readiness for the Industrial Revolution. This is because trade unions from labor and workers' associations play a very important role in bridging communication relations with company management so that what is desired of workers / workers is to adapt to the development of the industrial revolution itself. Where workers must improve their competence in facing changes in the field of digital technology by formulating work programs that are aligned in encouraging productivity of company performance.